3555 Intrahepatic Cholestasis of Pregnancy (ICP) is associated with higher prevalence of NAFLD: a case-control study. (27th March 2019) - Monrose, Erica; Zamudio, Andres Ramirez; Aristide, Alaina; Navalurkar, Reema; Bedekar, Rashi; Ferrara, Lauren; Kushner, Tatyana
Abstract : OBJECTIVES/SPECIFIC AIMS: Intrahepatic Cholestasis of Pregnancy (ICP) is the most common liver disease unique to pregnancy. Progression of non-alcoholic fatty liver disease (NAFLD) has been linked to the dysregulation of bile acid homeostasis. However, an association of NAFLD with ICP has not been previously evaluated. We evaluated the association between ICP and NAFLD and associated metabolic risk factors, including obesity, dyslipidemia, hypertension, and diabetes. METHODS/STUDY POPULATION: A single-center, retrospective case-control study was conducted between January and December 2017 in a primarily Latina population in a New York City health system with a high prevalence of ICP, 2.53% of all pregnancies (compared to 0.32% nationally). Pearson's chi-square or Fisher's exact test and Wilcoxon rank-sum tests were performed to evaluate association of ICP with categorical variables and continuous variables, respectively. Unadjusted odds ratios (OR) with 95% confidence intervals (95% CI) were calculated in comparison with the control group for clinically significant outcomes. RESULTS/ANTICIPATED RESULTS: 149 pregnancies complicated by ICP were identified from electronic medical records; 200 controls were matched by delivery year. Hispanic women were more likely to be diagnosed with ICP than non-Hispanic women (OR 1.90, 95% CI 1.87-3.03). ICP and control patients were similar for: median age (OR 1.02, 95% CI.99-1.06), nulliparity (OR.79, 95% CI.48-1.30) and prevalence of hepatitis C (OR 1.35, 95% CI.08-21.67). In regards to metabolic risk factors, ICP patients and control patients were similar in prevalence of obesity (body mass index>30kg/m^2; OR 1.01, 95% CI.62-1.61), hemoglobin A1c>5.5% (OR.80, 95% CI.34-1.9), total cholesterol >200 mg/dL (OR 4.15, 95% CI.83-20.84), and prevalence of hypertension (OR.69, 95% CI.31-1.52). Median bile acid levels were 30.6 µmol/L (IQR 11.6, 32.7) in the ICP group. ICP patients had higher median alanine aminotransferase (ALT) (32 vs. 16 U/L, p<.0001), alkaline phosphatase (181 vs 128 U/L, p<.0001) and total bilirubin levels (0.5 vs 0.35, p<.0001) compared to controls. ICP patients were more likely to have ALT levels > 50 U/L (2 times the upper limit of normal; OR 3.22, 95% CI 1.48-7.03). ICP patients were significantly more likely to have a history of biliary disease (OR 3.29, 95% CI 1.39-7.80). ICP patients were more likely to have evidence of steatosis on liver imaging (OR 4.69, 95% CI 1.68-13.12) than non-ICP patients. When evaluating a diagnosis of NAFLD based on ICD-10 code or evidence of steatosis on liver imaging, ICP patients were significantly more likely to have a diagnosis of NAFLD than controls (OR 5.7, 95% CI 2.08-15.65). DISCUSSION/SIGNIFICANCE OF IMPACT: ICP appears to be associated with NAFLD independently of metabolic risk factors such as obesity, dyslipidemia, hypertension, and diabetes, suggesting a direct link between NAFLD and ICP. If findings are confirmed, ICP patients, especially those with elevated ALT, would benefit from screening for NAFLD and linkage to liver specialty care postpartum.